ANALISIS PENGARUH PENGETAHUAN, POLA MAKAN, DAN AKTIVITAS FISIK TERHADAP KEJADIAN HIPERTENSI DI PUSKESMAS SEMULA JADI KOTA TANJUNG BALAI TAHUN 2022 - simanjuntak, irma (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2023)
ABSTRACT Hypertension is a condition when the pressure in the blood vessel increasing chronically.The Increasing of cases of hypertension is caused by various factors, including : knowledge less, unhealthy life style such as diet, physical activity, smoking habit, and other factors. Controlling of hypertension could doing by increasing knowledge and healty life style. Date obtained from Primary Health Center Semula Jadi Kota Tanjung Balai showed increased cases of hypertension was that in 2019, there were 389 cases of hypertension, in 2020 there were 391 cases of hypertension, and in 2021 there were 398 cases of hypertension. This study aims to analyze the effect of knowledge, diet and physical activitiy of the hypertension at Primary Health Center Semula Jadi Kota Tanjung Balai in 2022. This type of study is a quantitative analytic with cross sectional study. The population of case in this study were all patients diagnosed with hypertension and patients diagnosed non-hypertension is control that came for treatment at Primary Health Care Semula Jadi Kota Tanjung Balai and The samples were 96 samples. Method of data analysis use univariate analysis, bivariate analysis and multivariate analysis with multiple logistic regression test. The results of the study statistically showed that knowledge and diet related of hypertension of hypertension controlling (p 0.05). The results of multiple logistic regression test were known variables that related to hypertension of hypertension controlling are knowledge (OR = 3.13) and diet (OR = 2.82). Knowledge was the most dominant factor which influencing the hypertension of hypertension controlling. It is suggested that it is necessary to increasing knowledge and information about healthy lifestyles by maintaining a healthy diet to the community through health promotion and education about the importance of knowledge and good diet so that it can prevention of hypertension. Keywords: Knowledge, Diet, Physical Activity, Hypertension